Avoiding inappropriate therapy of single‐lead implantable cardioverter‐defibrillator by using atrial‐sensing electrodes. (5th October 2018) - Kurt, Muhammed; Jathanna, Nikesh; Babady, Mehran; Schmidt, Jan; Müller, Patrick; Gerguri, Shqipe; Clasen, Lukas; Bejinariu, Alexandru; Kelm, Malte; Fürnkranz, Alexander; Makimoto, Hisaki
Abstract: Introduction: The single‐chamber implantable cardioverter‐defibrillator (ICD) can be associated with more frequent inappropriate therapies compared with dual‐chamber ICDs, when they are accompanied by a simpler implantation procedure. The aim of this study was to investigate whether the use of a single‐lead ICD system with atrial‐sensing electrodes results in a reduction of inappropriate ICD therapy. Methods and Results: The study population consisted of 212 consecutive patients, who underwent primary prophylactic single‐lead ICD implantation at our institute. A ventricular lead with atrial‐sensing electrodes was implanted in 77 patients (36%; Group‐VDD) and a ventricular lead without atrial‐sensing electrodes was implanted in 135 patients (64%; Group‐VVI). Procedural and follow‐up data were collected in a prospective registry. A higher prevalence of atrial fibrillation was present in Group‐VDD. There were no other significant differences in patient baseline characteristics (age, sex, and other comorbidities) or follow‐up period between the two groups. The operative parameters including fluoroscopic burden showed no significant differences between Group‐VDD and Group‐VVI. During a mean follow‐up period of 697 ± 392 days, 26 patients (12%) experienced appropriate ICD therapies and 13 patients (6%) suffered inappropriate ICD therapies. The incidence of inappropriate ICD therapies in Group‐VDD was significantly lower as compared to that of Group‐VVI (1/77 [1%] vs 12/135 [9%]; log‐rank, P = 0.028). The incidence of appropriate ICD therapies and the occurrence of device‐related complications showed no significant difference between the two groups. Conclusion: Single‐lead ICD with atrial‐sensing electrodes shows a lower incidence of inappropriate ICD therapy compared with the absence of atrial‐sensing electrodes, without additional operative burden or increased complications.